Family History of Crohn's Disease (CD) May Be a Risk Factor for Developing de novo CD following Ileal Pouch Anal Anastomosis (IPAA) for Ulcerative Colitis (UC). (28th October 2020) - Li, H; Arslan, M; Fu, Z; Lee, H; Mikula, M
Abstract: Introduction/Objective: A subset of patients with an established diagnosis of UC develops signs of CD (de novo CD) following IPAA. While the etiology and risk factors of de novo CD remain largely unknown, preliminary studies have shown controversial results regarding family history of inflammatory bowel disease (IBD) and smoking history. Methods: Patients that underwent IPAA for UC, with at least 1 year of follow-up, were identified (n=161; 1996 to 2018). We retrospectively reviewed the electronic medical records. Patients that were diagnosed with de novo CD during the follow-up period were further identified. Smoking history and family history of IBD were evaluated. Chi square test was performed to compare the frequencies. Odds ratio (OR) and 95% confidence intervals (CIs) were estimated by logistic regression model. P<0.05 was considered statistically significant. Results: 29 de novo CD were identified. At the time of proctocolectomy, the family history of IBD and smoking history was documented in 152 UC patients including 27 that subsequently developed de novo CD. 23 of 152 had a family history of IBD (12 UC, 9 CD and 2 IBD, NOS). 19/129 (14.7%) UC patients without a family history of any type of IBD, 4/9 (44.4%) with a family history of CD, and 4/12 (33.3%) with a family history of UC developed de novo CD. Patients with a family history of CD were more likely to develop de novo CD post IPAA than those without a family history of any type of IBD (OR 4.63, 95% CI 1.14-18.82, p=0.03). Family history of UC did not correlate with development of de novo CD (OR 2.90; 95% CI 0.79-10.57, p=0.108). At the time of proctocoletomy, 11 were current smokers, 25 were former smokers, and 116 never smoked. In de novo CD group, there were 4/27 (14.8 %) former smokers and 23/27 (85.2 %) never smokers. No de novo CD patient was current smoker. In the UC group that remained as UC following IPAA, 11/125 (8.8%) were current smokers, 21/125 (16.8 %) former smokers, and 93/125 (74.4 %) were never smokers. Current smoking status was not associated with development of de novo CD (p = 0.214). Conclusion: Family history of CD may be a risk factor for developing de novo CD following IPAA for UC. Current smoking status was not associated with development of de novo CD following IPAA for UC.